2011
DOI: 10.5194/hessd-8-4979-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the contribution of glacier runoff to streamflow in the upper Columbia River basin, Canada

Abstract: Glacier melt provides important contributions to streamflow in many mountainous regions. Hydrologic model calibration in glacier-fed catchments is difficult because errors in modelling snow accumulation can be offset by compensating errors in glacier melt. This problem is particularly severe in catchments with modest glacier cover, where goodness-of-fit statistics such as the Nash-Sutcliffe model efficiency may not be highly sensitive to the streamflow variance associated with glacier melt. While glacier mass … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
94
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 26 publications
3
94
0
Order By: Relevance
“…Our results provide preliminary estimates of glacier contributions to streamflow in the basin, broadly consistent with the hydrological modelling results of Jost et al (2012), which assess a neighbouring basin with similar glacier extent. Glacier contributions to Illecillewaet Basin averaged 112 ± 12 × 10 6 m 3 from 2009 to 2011, with 66% of this from seasonal snow and 34% from glacier ice and firn.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our results provide preliminary estimates of glacier contributions to streamflow in the basin, broadly consistent with the hydrological modelling results of Jost et al (2012), which assess a neighbouring basin with similar glacier extent. Glacier contributions to Illecillewaet Basin averaged 112 ± 12 × 10 6 m 3 from 2009 to 2011, with 66% of this from seasonal snow and 34% from glacier ice and firn.…”
Section: Discussionsupporting
confidence: 77%
“…Glacier melt also has a cooling effect on streams because of the colder meltwater and higher flows; this reduces the sensitivity to energy inputs and maintains habitat for cold-water species in downstream rivers (Moore, 2006). There has been limited glaciological research in the CCRB, but modelling efforts in the Mica sub-basin indicate that meltwater from glacier ice contributes up to 25-35% of streamflow in August and September (Jost, Moore, Menounos, & Wheate, 2012). This represents a vital freshwater resource to the Columbia River system, supporting municipalities, industry, hydroelectricity generation, irrigation, and ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of these effects for glaciers in Switzerland showed that the negative effect caused by glacier surface lowering compensated on average about 50% of the positive effect due to glacier area change . While changes in glacier geometry have been taken into account in hydrological modeling for climate impact analyses [e.g., Stahl et al, 2008;Huss et al, 2010;Nolin et al, 2010;Farinotti et al, 2012;Jost et al, 2012], to our knowledge they have so far not been considered for the attribution of observed discharge trends.…”
Section: Water Resources Researchmentioning
confidence: 99%
“…It is therefore necessary to include glacier mass balance estimates in the model calibration procedure [e.g., Schaefli et al, 2005;Stahl et al, 2008;Konz and Seibert, 2010;Mayr et al, 2013]. As mass balance data derived by the glaciological method are only available for few individual glaciers, geodetic glacier mass balances may be applied as an alternative [Jost et al, 2012].…”
Section: Water Resources Researchmentioning
confidence: 99%